Hepatic PPARα function and lipid metabolic pathways are dysregulated in polymicrobial sepsis - Lise Van Wyngene; Tineke Vanderhaeghen; Steven Timmermans; Jolien Vandewalle; Kelly Van Looveren; Jolien Souffriau; Charlotte Wallaeys; Melanie Eggermont; Sam Ernst; Evelien Van Hamme; Amanda Gonçalves; Guy Eelen; et al. (EMBO Molecular Medicine)
Abstract Despite intensive research and constant medical progress, sepsis remains one of the most urgent unmet medical needs of today. Most studies have been focused on the inflammatory component of the disease; however, recent advances support the notion that sepsis is accompanied by extensive metabolic perturbations. During times of limited caloric intake and high energy needs, the liver acts as the central metabolic hub in which PPARα is crucial to coordinate the breakdown of fatty acids. The role of hepatic PPARα in liver dysfunction during sepsis has hardly been explored. We demonstrate that sepsis leads to a starvation response that is hindered by the rapid decline of hepatic PPARα levels, causing excess free fatty acids, leading to lipotoxicity, and glycerol. In addition, treatment of mice with the PPARα agonist pemafibrate protects against bacterial sepsis by improving hepatic PPARα function, reducing lipotoxicity and tissue damage. Since lipolysis is also increased in sepsis patients and pemafibrate protects after the onset of sepsis, these findings may point toward new therapeutic leads in sepsis.